Navigating a Highly Protected Market: China’s Chery Automobile in Malaysia - Zhang, M.; Rasiah, R.; Lee, J.K.Y. (Taylor & Francis, 2017)
The economies of Malaysia and China have become increasingly integrated through trading and investment linkages. This article focuses on one aspect of this relationship, examining Chery, a Chinese car maker, and its internationalisation strategy and its localisation efforts in Malaysia. It does this by analysing Chery’s interaction with the host government, local partners and suppliers. Using an in-depth case study, it was found that Chery’s experience in navigating a set of complex state–society relations in Malaysia resulted from an adaptation of its business strategy to address protectionist and institutional constraints found in Malaysia. However, while relations between Chery, the local partner and government agencies have grown strongly, few interactions have evolved between Chery and local suppliers and national research and development facilities, limiting collective learning processes and production collaboration in Malaysia. The evidence also suggests that Chery’s present conundrum of low sales in the country could be solved through negotiations with the Malaysian government so as to evolve mutually beneficial partnerships with national automotive makers. The Malaysian government may also consider easing its protectionist measures to allow more foreign participation into the auto sector to stimulate growth and competitiveness.